FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Fianny Andrea; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to obtain empirical evidence regarding the effect of liquidity and capital structure on company performance with firm size as moderating variable. The research was conducted at manufacturing companies in the basic and chemical industry sectors, the consumer goods industry, and various industries for the 2019-2021 period. This study uses secondary data. This research was conducted with a sample of 78 company data with the technique used in this research is purposive sampling. Data processing in this study uses the E-views 12 program. The results obtained from this study indicate that liquidity and company size has a positive influence on company performance, while the capital structure has no positive effect on company performance. In addition, firm size can moderate the effect of liquidity on firm performance, while the firm size cannot moderate the effect of capital structure on firm performance.